Diseño de un instrumento para la evaluación de principios cooperativos para la Cooperativa de Ahorro y Crédito " Sierra Centro Ltda."De la ciudad de Latacunga por sus grupos de interés. - Guayta Toapanta, Nilton Alexis (2020)
The present investigation, which deals with the design of an instrument for the evaluation of cooperative principles in the Cooperativa de Ahorro y Crédito "Sierra Centro Ltda." of the city of Latacunga by its stakeholders, part of the problem that certain Savings and Credit Cooperatives of the city of Latacunga do not carry out evaluations on the application of the cooperative principles related to their social balance, they do not have instruments that allow the mentioned, evaluation taking into account the perception of the interest groups of the cooperative; The problem being that the level of compliance with the cooperative principles influences the perception of the cooperative's interest groups, therefore, the objective of this research was to design an instrument for evaluating the level of compliance with the Cooperative Principles Through the perception of the interest groups of the Cooperativa de Ahorro y Crédito "Sierra Centro Ltda.", it has a wide bibliographic support and based on a methodological process identifying the seven cooperative principles established by the International Cooperative Alliance and confirmed by the Law of Popular and Solidarity Economy of Ecuador, which are: Open and voluntary membership, Democratic control of members, Economic participation of members, Autonomy and independence, Education, training and information, Cooperation between cooperatives and Interest in the community; principles applied for the social balance of the Cooperative and considered in the evaluation instrument proposed for the Cooperative and; finally approved through a validation process with an expert and its users.